Antisense‐mediated exon skipping: a therapeutic strategy for titin‐based dilated cardiomyopathy. Issue 5 (10th March 2015) - Gramlich, Michael; Pane, Luna Simona; Zhou, Qifeng; Chen, Zhifen; Murgia, Marta; Schötterl, Sonja; Goedel, Alexander; Metzger, Katja; Brade, Thomas; Parrotta, Elvira; Schaller, Martin; Gerull, Brenda; et al.
<x xml:space="preserve">Abstract</x> Truncating mutations in the giant sarcomeric protein titin (TTN) are a major cause for inherited forms of dilated cardiomyopathy (DCM). Antisense oligonucleotides (AON)‐mediated exon skipping is shown here to be a promising strategy as potential treatment option for DCM.